Gene Co-expression Network Analysis Suggests the Existence of Transcriptional Modules Containing a High Proportion of Transcriptionally Differentiated Homoeologs in Hexaploid Wheat - Takahagi, Kotaro; Inoue, Komaki; Mochida, Keiichi (Frontiers in Plant Science, 2018)
Genome duplications aid in the formation of novel molecular networks through regulatory differentiation of the duplicated genes and facilitate adaptation to environmental change. Hexaploid wheat, Triticum aestivum, contains three homoeologous chromosome sets, the A-, B-, and D-subgenomes, which evolved through interspecific hybridization and subsequent whole-genome duplication. The divergent expression patterns of the homoeologs in hexaploid wheat suggest that they have undergone transcriptional and/or functional differentiation during wheat evolution. However, the distribution of transcriptionally differentiated homoeologs in gene regulatory networks and their related biological functions in hexaploid wheat are still largely unexplored. Therefore, we retrieved 727 publicly available wheat RNA-sequencing (RNA-seq) datasets from various tissues, developmental stages, and conditions, and identified 10,415 expressed homoeologous triplets. Examining the co-expression modules in the wheat transcriptome, we found that 66% of the expressed homoeologous triplets possess all three homoeologs grouped in the same co-expression modules. Among these, 15 triplets contain co-expressed homoeologs with differential expression levels between homoeoalleles across ≥95% of the 727 RNA-seq datasets, suggesting a consistent trend of homoeolog expression bias. In addition, we identified 2,831 differentiated homoeologs that showed gene expression patterns that deviated from those of the other two homoeologs. We found that seven co-expression modules contained a high proportion of such differentiated homoeologs, which accounted for ≥20% of the genes in each module. We also found that five of the co-expression modules are abundantly composed of genes involved in biological processes such as chloroplast biogenesis, RNA metabolism, putative defense response, putative posttranscriptional modification, and lipid metabolism, thereby suggesting that, the differentiated homoeologs might highly contribute to these biological functions in the gene network of hexaploid wheat.